Analysis of the Implementation of Islamic Business Ethics at Manna Supermarket Yogyakarta Campus - Salsabilla, Saskia; Hutagalung, Muhammad Abrar Kasmin (Fakultas Ekonomi dan Bisnis, Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
This study aims to analyze the implementation of Islamic business ethics at Manna Supermarket Yogyakarta, focusing on the principles of shidq (honesty), ‘adl (justice), amanah (trustworthiness), and ihsan (benevolence). The research used a descriptive qualitative method, with data collected through interviews, observations, and documentation. Informants included one HR Manager and three customers. The findings indicate that the application of Islamic business ethics has been effectively implemented. The principle of shidq is reflected in transparent pricing and product authenticity, while ‘adl is demonstrated through equal service for all customers. The principle of amanah appears in the supermarket’s social responsibility toward community welfare around the campus. Meanwhile, ihsan is shown through employee friendliness, assistance, and willingness to provide additional service. However, challenges remain, such as limited understanding of Islamic ethical values among employees and inconsistencies in their practical application. This study contributes to the advancement of Islamic-based retail business practices and serves as a valuable academic reference for implementing Islamic business ethics in the modern retail sector.